2010
DOI: 10.1007/s11676-010-0096-x
|View full text |Cite
|
Sign up to set email alerts
|

Soil chemical properties under modern and traditional farming systems at Khagrachari, Chittagong Hill Tracts, Bangladesh

Abstract: Land degradation in Chittagong hill tracts has been taking place due to shrinkage of forest cover, policy weakness, population explosion, and inappropriate hill farming system. Modern farming system in the Chittagong hill tracts like Sloping Agricultural Land Technology (SALT) is practiced to provide a new strategy for developing lands for economic productivity and bio-diversity conservation through establishment of ecological community rather than traditional shifting cultivation which is no longer sustainabl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
6
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(7 citation statements)
references
References 26 publications
1
6
0
Order By: Relevance
“…Moreover, these three locations also contained lower organic matter compared to adjacent mixed planted forest of several tree species having good canopy coverage. Biswas et al (2010) also found in this mountainous region higher pH on land just after sowing at Alutila of Kharacharichari district. Gafur et al (2000) reported higher pH from shifting cultivated area with more run-off compared to vegetated land comprised of mixed trees of horticulture and forest species in Soil Conservation and Watershed Management Center at Banderban.…”
Section: Discussionsupporting
confidence: 56%
See 1 more Smart Citation
“…Moreover, these three locations also contained lower organic matter compared to adjacent mixed planted forest of several tree species having good canopy coverage. Biswas et al (2010) also found in this mountainous region higher pH on land just after sowing at Alutila of Kharacharichari district. Gafur et al (2000) reported higher pH from shifting cultivated area with more run-off compared to vegetated land comprised of mixed trees of horticulture and forest species in Soil Conservation and Watershed Management Center at Banderban.…”
Section: Discussionsupporting
confidence: 56%
“…Various reports (Miah et al 2010;Biswas et al 2010;Gafur et al 2000) indicate that shifting cultivation may either decrease or increase soil pH depending on cultivation stage, runoff condition and amount of organic matter present on the land. Higher pH in shifting cultivated land at three locations namely Burburichara, Maichhari and Langadu was associated with addition of ashes in soil from complete burning of earlier vegetation before sowing paddy seeds, turmeric and similar other crops and from deep hoeing of the soil.…”
Section: Discussionmentioning
confidence: 99%
“…The most emerging problems related to the case study area were formulated according to issues previously identified in the first stage. Environmental issues in the CHT include deforestation, illegal hunting, adverse effects of short rotation shifting cultivation (Khisa et al 2006;Biswas et al 2010), scarcity of clean drinking water, lack of adequate sanitation, hill cutting (mining and leveling), soil erosion, slope failures, flooding, and conversion of sensitive sites to agriculture (e.g., tobacco cultivation in the Matamuhri river floodplain; Chowdhury et al 2007a, b). The primary components and main principles of the preliminary PCIV set were communicated to the key informant group through meetings and phone/email contact, with the explicit understanding that every stakeholder could recommend alterations.…”
Section: Selection Of Key Informants and Groupsmentioning
confidence: 99%
“…The soils of CHT are mostly sandy (37 to 67%) and the rest of them are silt and clay [6]. Though the soils of CHT is not suitable for agriculture, frequent use of the same land towards biomass production reduces soil fertility and increase the level of toxic metals and various pollutants (Biswas et al, 2010).…”
Section: Introductionmentioning
confidence: 99%
“…The soils of CHT are mostly sandy (37 to 67%) and the rest of them are silt and clay [6]. Though the soils of CHT is not suitable for agriculture, frequent use of the same land towards biomass production reduces soil fertility and increase the level of toxic metals and various pollutants (Biswas et al, 2010). Also, contamination of soil including metal concentration is hampered by some other factors such as soil properties, such as pH, organic matter content, minerals, cation exchange capacity of the soil phase, balancing with other metal ions etc.…”
Section: Introductionmentioning
confidence: 99%